Physical, sexual, emotional and economic intimate partner violence and controlling behaviors during pregnancy and postpartum among women in Dar es Salaam, Tanzania - Mahenge, Bathsheba; Stöckl, Heidi; Abubakari, Abdulai; Mbwambo, Jessie; Jahn, Albrecht (PLOS ONE, 2016)
Background Intimate partner violence (IPV) during pregnancy and postpartum is a serious global health problem affecting millions of women worldwide. This study sought to determine the prevalence of different forms of IPV during pregnancy and postpartum and associated factors among women in Dar es Salaam, Tanzania. Methods We conducted a cross-sectional study among 500 women at one to nine months postpartum in three health facilities in the three districts of Dar es Salaam: Temeke, Kinondoni and Illala. Two trained research assistants administered the questionnaire, which aimed to examine sociodemographic characteristics and different forms of IPV. Results Of the 500 women who were interviewed, 18.8% experienced some physical and/or sexual violence during pregnancy. Forty-one women (9%) reported having experienced some physical and/or sexual violence at one to nine months postpartum. Physical and/or sexual IPV during pregnancy was associated with cohabiting (AOR 2.2, 95% CI 1.24-4.03) and having a partner who was 25 years old or younger (AOR 2.7, 95% CI 1.08-6.71). Postpartum, physical and/or sexual IPV was associated with having a partner who was 25 years old or younger (AOR 4.4, 95% CI 1.24-15.6). Conclusion We found that IPV is more prevalent during pregnancy than during the postpartum phase. There is also continuity and maintenance of IPV during and after pregnancy. These results call for policy and interventions to be tailored for pregnant and postpartum women.